2013
DOI: 10.4236/wja.2013.32015
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Attendance and Non-Attendance of Support Groups among HIV Positive Adults Attending an Antiretroviral Community Clinic at Ekurhuleni District, South Africa

Abstract: Health care facilities providing antiretroviral treatment (ART) to HIV positive people have seen a decline in the uptake and use of HIV support groups. A cross sectional survey was conducted to 1) determine the characteristics of HIV positive people who have and who have not attended support groups; 2) determine factors associated with attendance of support groups; and 3) investigate perceived barriers to participate in support groups among HIV positive adults attending an ART clinic in Gauteng, South Africa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…21 In addition, participants who attended support groups in a South African study were reported to be 1.6 times more likely to be taking HIV prophylaxis and ART medication than non-attenders. 22 This finding reaffirms the postulation that social support from PLWHA peers through a PLWHA support group mechanism plays an important part in ART adherence. Several studies in Mozambique, 23 Spain, 24 the USA 25 and Canada 26 have disclosed higher self-reported adherence among respondents in peer support groups when compared with respondents not in support groups.…”
Section: Discussionsupporting
confidence: 69%
“…21 In addition, participants who attended support groups in a South African study were reported to be 1.6 times more likely to be taking HIV prophylaxis and ART medication than non-attenders. 22 This finding reaffirms the postulation that social support from PLWHA peers through a PLWHA support group mechanism plays an important part in ART adherence. Several studies in Mozambique, 23 Spain, 24 the USA 25 and Canada 26 have disclosed higher self-reported adherence among respondents in peer support groups when compared with respondents not in support groups.…”
Section: Discussionsupporting
confidence: 69%
“…Increased participation of men in HIV support groups plays an important role as they are safe spaces in which men share experiences with their peers, receive peer support, work on their emotions and access peer counseling for grief and anger (CRS, 2012). More so, there has been an increased need to form gender-specific support groups, different designated meeting days and more flexible designs to improve male participation [ 12 , 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…For patients who work full-time, the hospital could offer counseling sessions outside business hours. These interventions have been trialed and found to be successful in other settings 1,28 . Thus, they may be worth the hospital investment for improved patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Counseling is one of the most utilized psychosocial interventions for patients with HIV and AIDS. 1 Although HIV/AIDS is a physical condition, it has a profound effect on more than just physical health. With the advent of anti-retroviral therapy (ART), HIV/AIDS has become a chronic condition over the past three decades.…”
mentioning
confidence: 99%
See 1 more Smart Citation